Expect the Unexpected - Case Series of Peripartum Cardiomyopathy (Journal of Pharmaceutical Negative Results, 2023)
Peripartum Cardiomyopathy (PPCM) is a serious and rare condition of unknown cause that affects childbearing woman. The symptoms of PPCM are likely to be confused with physiological changes associated with advanced pregnancy therefore high degree of suspicion should be present. In majority of the cases, the overall prognosis is good, although some patients may progress to irreversible heart failure. Early identification, diagnosis and prompt treatment at tertiary care hospitals reduces mortality and morbidity and improves the chances of complete recovery of heart function. Here we are presenting four clinical cases of peripartum cardiomyopathy, their course, treatment and outcome at Dr D.Y. Patil Medical College and Hospital, Pimpri, Pune, Maharashtra, who presented between January 2020 to November 2022. Ethical committee clearance was taken for this case study